Neoadjuvant therapy in elderly patients receiving FOLFIRINOX or gemcitabine/nab-paclitaxel for borderline resectable or locally advanced pancreatic cancer is feasible and lead to a similar oncological outcome compared to non-aged patients – Results of the RESPECT-Study. (December 2020) - Weniger, Maximilian; Moir, John; Damm, Marko; Maggino, Laura; Kordes, Maximilian; Rosendahl, Jonas; Ceyhan, Güralp O.; Schorn, Stephan; ,; Schmid, Daniel; D'Haese, Jan G.; Böck, Stephan; et al.
Abstract: Introduction: The number of people aged 60 and above will rise from 46 million in 2015 to 157 in 2050 million, exceeding 30% of the population in many western countries. Consequently, the demand for oncological therapy for elderly patients will increase within the next decades. Currently, sufficient data on neoadjuvant therapy (NTx) of pancreatic cancer in elderly patients are lacking. Methods: Data of a multinational, retrospective database were screened for patients having received preoperative FOLFIRINOX (FFx) or Gemcitabine/nab-paclitaxel (GNP) for locally advanced and borderline resectable pancreatic cancer (LAPC/BRPC) before June 2017. Data were included in an intention-to-treat-analysis and outcomes were compared between non-aged and elderly patients using a cut-off age of 63 (comparison 1) and 70 years (comparison 2). Results: Of 165 patients receiving NTx, 76 and 33 were older than 63 and 70 years. Baseline characteristics revealed that elderly patients preferably undergo GNP (comparison 1: p = 0.063; comparison2: p = 0.005), with less cycles of NTx (comparison 1: p = 0.057). Whereas reductions of NTx dosage was more common in elderly patients in comparison 1 (p = 0.003), resection rates (p = 0.575; p = 1.000) and median survival (p = 0.406; p = 0.499) were not different. Whereas resected patients showed no differences in survival (p = 0.328; p = 0.132), patients aged >70 years showed a decreased progression-free survival (p = 0.019). Conclusion: Elderly patients treated with NTx show encouragingly high resection rates. If comorbidities allow for FFx or GNP, elderly patients with LAPC/BRPC can offered NTx with the prospect of survival comparable to younger patients. Highlights: Elderly PDAC-patients show encouraging resection rates after neoadjuvant chemotherapy. After resection, OS and PFS were comparable between elderly and non-aged patients. Neoadjuvant chemotherapy is feasible in selected elderly patients with BRPC/LAPC.